The Effect of Political Contestation on Investor Reaction: Evidence from Indonesia Sharia Stock - Nasution, Ananta Hagabean; Fadhillah, Penny Rahmah; Zusryn, Alyta Shabrina (Lembaga Penelitian Universitas YARSI, 2023)
Political events can cause uncertainty in the business environment and affect stock returns. This study aims to examine the reaction of sharia stock investor to political events in 2019. Some previous studies found that the influence of political events in Indonesia on investors' reactions is not yet conclusive. Therefore, this research utilized five political events during the general election they are: candidates inauguration, candidates’ final debate, quick count announcement, Election Commission (KPU) announcement, Constitutional Court (MK) announcement. This research used cumulative average abnormal return (CAAR) and average abnormal return (AAR) values as indicators in detecting investor reactions and used actively traded stocks listed on the Indonesian Sharia Stock Index (ISSI) from 2017 to 2019. The results of this study indicate that there is a negative reaction on t-1 before the debate of candidates. Furthermore, the opposite results occurred during the announcement of the presidential election results conducted by the Election Commission (KPU). This result indicates that investors quickly get information about political uncertainty. The implication is that political events are one of the relevant event studies to determine sharia stock prices to investors.